Wound Healing by Allogeneic Transplantation of Specific Subpopulation From Human Umbilical Cord Mesenchymal Stem Cells - Palma, María Belén (2021)
In normal physiological conditions, restoration of a functional epidermal barrier is highly efficient; nevertheless, when it fails, one of the main consequences is a chronic ulcerative skin defect, one of the most frequently recognized complications of diabetes. Most of these chronic venous ulcers do not heal with conventional treatment, leading to the appearance of infections and complications in the patient. Treatments based on the use of autologous mesenchymal stem cells (MSC) have been successful; however, its implementation entails complications. The umbilical cord offers an unlimited source of adult MSC (ucMSC) from the Wharton’s jelly tissue with the same relevant features for clinical applicability and avoiding difficulties. It has recently been characterized by one specific subpopulation derived from ucMSC, the differentiated mesenchymal cells (DMCs). This subpopulation expresses the human leukocyte antigen-G (HLA-G) molecule, a strong immunosuppressive checkpoint, and vascular endothelial growth factor (VEGF), the most potent angiogenic factor. Considering the importance of developing a more effective therapy for wound treatment, especially ulcerative skin lesions, we analyzed DMC safety, efficacy, and therapeutic potential. By immunohistochemistry, umbilical cords HLA-G and VEGF positive were selected. Flow cytometry revealed that 90% of the DMC subpopulation are HLA-Gþ, CD44þ, CD73þ, CD29þ, CD105þ, CD90þ, and HLA-DR . Reverse transcription-polymerase chain reaction revealed the expression of HLA-G in all of DMC subpopulations. Upon co-culture with the DMC, peripheral blood mononuclear cell proliferation was inhibited by 50%. In a xenograft transplantation assay, DMC improved wound healing with no signs of rejection of the transplanted cells in immunocompetent mice. This study confirms that HLA-G allows allogeneic cell transplantation, and VEGF is fundamental for the restoration of the failure in blood supply. DMC population has positive effects on wound healing by promoting local angiogenesis in skin lesions. DMC could play a very important role in regenerative medicine and could be a novel allogeneic cell-therapeutic tool for wound healing.